Physical mapping and complementation analysis of transposon Tn5 mutations in Caulobacter crescentus: organization of transcriptional units in the hook gene cluster. - Ohta, N (1984)
Using the cloned DNA from the hook protein gene region of Caulobacter crescentus ( Ohta et al., Proc. Natl. Acad. Sci. U.S.A. 79:4863-4867, 1982), we have identified and physically mapped 19 Tn5-induced and 2 spontaneous insertion mutations to this region of the chromosome. These nonmotile mutants define a major cluster of fla genes that covers approximately 17 kilobases on the chromosome (hook gene cluster). Complementation analysis of the mutants using DNA fragments from the region subcloned in the broad host range plasmid pRK290 has shown that these fla genes are organized into at least five transcriptional units (I to V). Transcriptional unit II contains at least one gene in addition to the hook protein gene, which makes this the first operon described in C. crescentus. Expression of the hook protein gene and the genetically unlinked flagellin A and B genes by this set of mutants also furnishes additional insights into the hierarchial regulation of flagellar genes. We have found that the spontaneous insertion mutant ( SC511 ) of the hook protein gene ( flaK ) makes no flagellin A or B and that genes downstream from the hook protein gene are required in trans for expression of the hook protein operon and the flagellin A and B genes. Recombination and complementation results thus place flaK , flaJ , flaN , and flaO (R. C. Johnson and B. Ely , J. Bacteriol . 137:627-634, 1979) in the hook gene cluster, identify at least three new genes ( flbD , flbG , and flbF ), and suggest that this cluster may contain several additional, as yet unidentified, fla genes.